PERAN KONSORSIUM BAKTERI CULTURABLE TERHADAP PERCEPATAN DAN PENGENDALIAN KOROSI PADA BAJA KARBON ST 37 - Kusumawati, Elly
Corrosion in the installation pipe made of ST 37 carbon steel at the Cirata hydropower plant can be caused by microbiological influence corrosion (MIC). Based on previous research, the existence of floating net cages causes a decrease in reservoir water quality as indicated by an increase in iron-oxidizing bacteria (IOB), acid-producing bacteria (APB), nitrite-oxidizing bacteria (NOB), and biofilm-forming bacteria. The interaction between NOB and APB can increase the corrosion rate up to 10 times compared to abiotic control, while the interaction between IOB and biofilm-forming can increase the rate up to 5.5 times. However, the role of these four groups of bacteria in causing corrosion has not been evaluated. In previous studies, one isolate of biofilm-forming bacteria was also found which was able to reduce the corrosion rate by up to 47%. This corrosion rate inhibition capability needs to be further optimized. This study aims to: 1) identify the key bacterial isolates on corrosion (E, F, G, L, and O); 2) determine the increase in the corrosion rate of the consortium of IOB, APB, NOB, and biofilmforming bacteria; 3) determine the effect of the addition of O isolates on the prevention of corrosion-causing biofilms; and 4) determine the role of each group of bacteria in forming biofilms that cause corrosion of ST 37 carbon steel. Corrosion tests were carried out under 3 conditions, namely corrosive consortium (E:F:G:L) and treatment with the addition of O isolates in planktonic conditions (E:F:G:L:O), and biofilms ( O24:E:F:G:L). The corrosion acceleration test for ST 37 carbon steel was observed every 3 days for 30 days under aerobic, dark, static, and 25 – 270C conditions in a sterile reservoir water medium. The calculated data are corrosion rate, the weight of biofilm and corrosion products, pH, total dissolved solids (TDS), nitrate and sulfide concentrations, and abundance of bacteria in the planktonic and biofilm phases. The results of the identification of bacterial isolates E, F, G, L, and O using the 16S rRNA sequencing method respectively were Chryseobacterium spp. E, Pseudomonas kribbensis spp. F, Pseudomonas putida spp. G, Paracoccus contaminans spp. L, and Priestia megaterium spp. O. The corrosion rate caused by the consortium of E:F:G:L bacteria was 11.07 m/year or 2.4 times higher than the abiotic control. The addition of Priestia megaterium spp. O in the planktonic phase was able to reduce the corrosion rate of E:F:G:L up to 58.35%. Meanwhile, the addition of Priestia megaterium spp. O reduces the corrosion rate of E:F:G:L up to 37.58%. In biofilm formation, P. kribbensis spp. F, P. putida spp. G, and Priestia megaterium spp. O plays a role in the initial colonization process while the bacteria Chryseobacterium spp. E and Paracoccus contaminans spp. L plays a role in the microcolony formation phase to the maturation stage. In this study, the addition of Priestia megaterium spp. O in the planktonic phase has the potential as a biocontrol agent for corrosion of carbon steel ST 37 in the waters of the Cirata Reservoir.